Smart Apps Creator: Mathematics Scientific-Based Interactive Multimedia for Improving Acceleration Program Students’ HOTS - Qur’ani, Fauziyah Nafisatul; Wulan, Eka Resti; Syamsudin, Ahmad (Phenomenon : Jurnal Pendidikan MIPA, 2023)
It was found that the use of learning media in the form of modules and learning videos is not interactive so they make students feel bored and less active when the learning process. It causes students to have difficulty solving HOTS-type questions. Thus, this study aims to develop scientific-based interactive mathematics multimedia to increase the HOTS of accelerated students on similarity and congruence materials with the help of the Smart Apps Creator. This study uses the R&D method with the ADDIE model. The data analysis technique in this research is descriptive and uses paired samples t-test. The instruments are a questionnaire for material and media expert validation, a questionnaire for teacher and student responses, a pre-test, and a post-test.  The results of the validation of the material expert obtained the "Eligible" interpretation, the media expert obtained the "Very Eligible" interpretation obtained the "Eligible" interpretation. The results of the teacher's response, the student's response to the limited test, and the group test obtained the interpretation of "Very Eligible". By using the paired samples t-test, show a significance level of 0.000 was obtained where 0.000 < 0.05, which means that there was an increase in the HOTS of class VIII-J students after using the developed interactive mathematics multimedia. Based on the results obtained, the interactive mathematics multimedia developed can be used as a learning media for students.